Hardware Causing Hard Times: Use of the SuperNO2 VA™ Nasal PAP Device to Address Airway Challenges Caused by Eroding Mandibular Hardware - Michael Marotta; Geoffrey S. Kilgore (Research and Practice in Anesthesiology, 2019)
Background Maintenance of the airway and adequate ventilation are essential for the anesthetized patient and may be compromised in patients with pan-facial trauma, abnormal dentition, abnormal mandibular space, or presence of dental hardware. We present an unusual case of a patient with a lack of natural mandibular structure and exposed mechanical hardware with fistula complicating intubation and ventilation prior to surgery. Case Presentation A 35-year-old male with a history of a self-inflicted gunshot to the left submandibular region approximately 6 years prior was scheduled for urgent mandibular hardware removal, closure of left facial fistula, and removal of several teeth. Pre-oxygenation and ventilation were complicated by extruding hardware and eroded skin, causing interference with a conventional facemask seal. The patient was pre-oxygenated using the SuperNO2 VA™ nasal mask with which an adequate seal was achieved without use of a nasal trumpet and with a modified grip. Tracheal intubation via oral video laryngoscopy was successful, and the case proceeded uneventfully. Conclusion Adequate ventilation and airway maintenance can be difficult to achieve in patients with abnormal facial structure or mandibular mechanical hardware using conventional methods. The SuperNO2 VA™ nasal mask can address airway issues for these patients peri-operatively.